KEBIJAKAN PENEGAKAN HUKUM TINDAK PIDANA PENEMPATAN TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI - Dian Aji Setiawan; Elfrida Ratnawati Gultom (LPPM Universitas Ekasakti Padang, 2023)
Law enforcement against crime relates with placement of Indonesian migrant worker abroad according to Indonesian rules number 39 of 2004 about placement and protection of Indonesian migrant worker Abroad that relation to protection of Indonesian migrant worker. But the reality of legislation is more many set concerning placement rather than protection, and the law is not synchronization with others legislations, whether operate vertical or horizontal, and that has conflicts of authority which raises the dualism of Institutional between BNP2TKI and Ministry of Manpower RI. The objectives of research for analyze: Policy of law enforcement placement of Indonesian migrant worker abroad; protection of criminal law for Indonesian migrant worker abroad; And others crime law enforcement in placement of Indonesian migrant worker abroad. This research is normative juridical research is qualitative, based to primary, secondary and tertiary data, through data collection documentaries and interviews, analyses in qualitative. Presenting conclusion: Policy law enforcement of Indonesian migrant worker to empower Police of Indonesian Investigator who are employed in BNP2TK1, and cases handled by investigators of PPNS BNP2TK1 is just for limited crime law of administration; criminal law protection of Indonesian migrant worker placement abroad is hopeless, because there is not to have synchronization of rules, also legislation is more emphasize of Indonesian migrant worker placement aspect is not protection aspect; and my suggestions: Indonesian police investigator who are employed in BNP2TKI should be empowered; subscribe regulation with placement and protection of Indonesian migrant workers abroad into immediately amendment; BNP2TKI as a non Departmental Government Institutions residing in and responsible indicated to the President, must be independent and free as an institution independent opened, tripartite, proactive, and funded well.